Governance and Gender Dynamics in Global Value Chains. A Case Study of the Industrial Dairy Value Chain in Matiguaś, Nicaragua - Marina Hülssiep (Südwind-Verlag, 2019)
The Master thesis of Ms Marina Hülssiep with the title "Governance and gender dynamics in global value chains. A case study of the industrial dairy value chain in Matiguaś, Nicaragua" takes issue with the phenomenon of global value chains (GVC). Given the large-scale territorial reorganization of production at the global level since the 1970s, which has also importantly included the economies of the Global South, GVC analysis has become an important field of inquiry also in development studies. Ms Hülssiep applies a GVC lens to study an economic sector - the dairy industry - that is of particular importance for the rural economy of many Low-Income Countries, in order to investigate gendered power structures and the role of women in dairy production. Through this approach, she combines GVC analysis with empirical gender studies to shed light on the potentials and limits of economic empowerment of women in a particular region in Nicaragua, a long-standing focus country of Austrian Development Cooperation. Given the eminent role of gender policies in European and Austrian Development Cooperation, the novel methodological approach applied in this study is both of relevance to a gender-sensitive approach to applied development research, and contributes to enlarging the knowledge base for gender programs and activities in development cooperation in general and Austrian development cooperation in particular.
Keywords: 330